Evaluating the Efficiency of Industrialization Process in Prefabricated Residential Buildings Using a Fuzzy Multicriteria Decision-Making Method. (26th September 2017) - Liang, Huakang; Zhang, Shoujian; Su, Yikun
Abstract : To alleviate the housing pressure and achieve a sustainable society, prefabricated residential building (PRB) has witnessed rapid growth in recent years. The usage of prefabricated components in the building represents a significant indicator that is traditionally used to differentiate the PRB from the traditional building. However, it cannot provide details on the efficiency of the industrialization process in the PRB. The main goal of this paper is to develop a composite index to measure the multidimensional concept of industrialization efficiency. Fuzzy Analytic Hierarchy Process (fuzzy AHP) and fuzzy Technique for Order Preference by Similarity to Ideal Solution (fuzzy TOPSIS) are applied to combine the hierarchical structure of indicators into one overall index. Finally, the industrialization efficiency assessment of three PRBs is chosen as a case to illustrate the effectiveness of the method. It can effectively quantify experts' linguistic expressions on the performance of the PRB in different established indicators. This research can provide a decision support tool to assess and continuously promote the improvement of industrialization production in the housing industry.